BLOOD PRESSURE LEVELS AND BODY MASS INDEX IN ADULTS WITH DOWN SYNDROME. (June 2018) - De Rosa, M.L.; Gioia, L.; Ferrante, L.; Ferrara, N.
Abstract : Objective: Increased life expectancy among people (p) with Down syndrome (DS) has introduced new environmental factors that may affect blood pressure (BP) and/or lead to obesity in this p. The aim here was to investigate BP levels and body mass index (BMI) in p with DS, correlating these data with the p' sex and age. Design and method: Analytical cross-sectional observational study conducted in our ambulatory in Naples, Italy 37 p were included. BP was measured in accordance with the established guidelines. BMI was calculated by dividing the weight by the height squared (kg/m2). Results: Sex had no influence on BMI; nor did systolic BP (SBP) or diastolic BP (DBP). The age range was from 18 to 62 yrs. No correlation was observed between increasing age and greater BMI or BP. 18 p(49%) presented lower BP than 90 × 60 mmHg, 18(49%) normal BP and one hypertension. BMI ranged from 18 to 48 kg/m2 (mean of 28.8 ± 3.92 kg/m2): 21% had normal weight; 39% were overweight; and 25% had obesity class I, 10% class II and 5% class III. Higher BMI was associated with significantly greater SBP and DBP (P = 0.0175 and P = 0.0015). Conclusions: Sex and age did not influence SBP, DBP or BMI in p with DS. Higher BMI was associated with greater BP (both systolic and diastolic). We conclude that BP is low in DS and that this is a feature of the disease rather than of the protected environment in which p live. A mechanism related to trisomy 21 is likely, and there may be a link with Alzheimer's disease (AD) because BP is also low in AD and a high proportion of DS develop this disease. If, as is likely, BP is lowered in Alzheimer's by the neuropathy, the same neuropathy developing early in DS may also reduce BP